Morphology of some marine benthic Dinoflagellates (Dinophyceae) of Prorocentrum based on light and scanning electron microscopy - Badaruddin, Zailiazwa; Mohammad Noor, Normawaty; Anton, Ann; Wei Lie, Grace Joy Chin (2010)
Marine benthic dinoflagellate smainly Prarocentrumspecies have been reported to produce diarrhetic shellfish @sP) genus Prorocentrum, toxin and this toxin can causes gastoointestinal disease in human. In identification of the the seYeral morphological characteristics have been used ia. cellsize, omamentation of thecal plates, number ofplatelets in the periflagellar area and mode of liviug fulanktonic aid/or benthic). To date there are more tlnn 20 species of benthic Fro ro"";; tp;;". hur" been described based on these species' characteristics but sometimes confusion occurred due to_overlafping characteristics among closely allied In this study morphological feature of 5 species of proroiintir*and 2 strains of prorocentrum collected lima Differences from Banggi Island, sabah were detennined based on iigi, *a scanning Electron Microscopy. on cell size, thecal plate omamentation and numb";;Gilil;""";ildrar discussed' Detail area \ryere description of each species willprovide aaaiuonaiinforrnation Prorocentrum in species delineation of species